2009
DOI: 10.2478/v10001-009-0032-5
|View full text |Cite
|
Sign up to set email alerts
|

The essential oil of turpentine and its major volatile fraction (α- and β-pinenes): a review

Abstract: This paper provides a summary review of the major biological features concerning the essential oil of turpentine, its origin and use in traditional and modern medicine. More precisely, the safety of this volatile fraction to human health, and the medical, biological and environmental effects of the two major compounds of this fraction (α-and β-pinenes) have been discussed. Key words:Spirits of turpentine, α-pinene, β-pinene Received: July 1, 2009. Accepted : September 28, 2009. Address reprint request to B. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
106
0
17

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(124 citation statements)
references
References 76 publications
1
106
0
17
Order By: Relevance
“…The highly lipophilic and volatile essential oils of conifer trees, such as pinenes and other bicyclic monoterpenes, may cause toxicity upon inhalation, cutaneous exposure, or massive oral ingestion (Mercier et al, 2009). By contrast, the toxicity of the resiniferous ingredients in larch turpentines, including larixol or larixyl acetate has not been reported in detail.…”
Section: Larixyl Acetate Is a Trpc6 Inhibitormentioning
confidence: 94%
“…The highly lipophilic and volatile essential oils of conifer trees, such as pinenes and other bicyclic monoterpenes, may cause toxicity upon inhalation, cutaneous exposure, or massive oral ingestion (Mercier et al, 2009). By contrast, the toxicity of the resiniferous ingredients in larch turpentines, including larixol or larixyl acetate has not been reported in detail.…”
Section: Larixyl Acetate Is a Trpc6 Inhibitormentioning
confidence: 94%
“…Both α-and β-pinene have been reported as sedatives (Mercier et al, 2009) and analgesics (Erazo et al, 2006). Kasanen et al (1998) also reported that all pinenes induced sedation followed by signs of anesthesia in mice.…”
Section: Transportation Experimentmentioning
confidence: 99%
“…To date, a crystal structure of CYP2A6 with environmentally important monoterpenes and a direct structural comparison of CYP2B and 2A enzymes in the presence of such hydrocarbons have been lacking. Sabinene is a major olefinic monoterpene derived from the volatile oils found in plants and is often used as an odorant and perfume additive and as an important constituent of plant oils in alternative medicine (Karp et al, 1987;Mercier et al, 2009;Harrison et al, 2013). In the current study, we sought to determine the first crystal structure of human CYP2A6 in complex with sabinene and compare it with the CYP2B6 complex.…”
Section: Introductionmentioning
confidence: 99%